(untitled) (Sains Humanika, 2022)
The implementation of Movement Control Order (MCO) nationwide due to the outbreak of Covid-19 has led to the closure of schools nationwide and created new norms in our national education system. This has indirectly accelerated the transition of Malaysia’s education system towards digital learning, which in line with the concept of 21st Century Learning. There are several challenges faced by teachers and students when doing online learning and face -to -face learning. Consequently, teachers’ experience in implementing online learning is potentially to be integrated with face -to -face learning once the school opens. Therefore, this study aims to design a blended learning method through Flipped Classroom approach using Google Classroom based on the advantages and disadvantages of online learning and face -to -face learning. The effectiveness of this learning method on student’s achievement of selected topic (‘Force’) in year 6 science subject is monitored and analysed. A total of 19 students was selected as respondents in this study. A purposive sampling was used to select schools as study locations and convenience sampling was used to select students as study’s respondents. The instrument of this study used pre-post test for both student achievement. The collected data has been analysed quantitatively, namely descriptive analysis and inferential analysis. Descriptive analysis was used to study the percentage and mean of comparison of pre-post test scores. Meanwhile, inferential analysis uses Wilcoxon test to observe the significance of mean difference for pre-post test scores. Both analyses were carried out using SPSS version 22 software. The results of the descriptive analysis found that there is an increment of about 29 % in mean scores on student achievement, respectively. The findings of this study are supported by the result of inferential analysis where a significant difference (Asymp. Sig. (2-tailed) = 0) in mean scores between pre-post tests on students’ achievement was obtained. In conclusion, the results of this study have had a positive impact on student achievement. Hopefully, through this study can provide exposure to teachers about the advantages of blended learning through Flipped Classroom approach using Google Classroom.